Modeling And Hydrodynamics Study Of A Thin Liquid Film Flow Over Horizontal Spinning Disk - Majnis, Mohd Fadhil (2010)
A thin liquid film flow over horizontal spinning disk under influence of centrifugal field is one of the implementation and method in process intensification. Hydrodynamics study and development of mechanistic model is strongly desirable to describe this film flow behaviors. Thus, Navier-Stokes equations and convective diffusion equation were used for thin film thickness prediction and to represent mixing characteristic over the spinning disk respectively. All the governing equations are solved numerically by finite difference method in two dimension configuration, with initial condition and boundary condition. Moreover, CFD software package, Fluent 6.3® was used to simulate a multiphase of volume of fraction (VOF) model of this flow. Then, experiments were carried out in a spinning disk test rig with variable speed of spinning to validate the developed mechanistic model, and to compare with simulation in CFD. The result obtained have showed that the developed mechanistic model and CFD model for thin liquid film thickness were in satisfactory agreement with the experimental results with R2 = 0.841 to 0.999. Meanwhile, the calculated mass transfer coefficients for mixing measures was compared with the work by Tsibranska et al. (2009). The results showed a similar trend in which the mass transfer coefficients increased as disk rotational speed increased. The calculated mass transfer coefficient and visualization of dye particles distribution in mixing characteristic in the present study showed that the speed of disk rotation was a significant parameter in enhancing the mass transfer in thin liquid film flow over a horizontal spinning disk.